Analisis Gaya Kepemimpinan, Kepuasan Kerja, Komitmen Organisasi dan Kompetensi terhadap Kinerja Pegawai - Basna, Frengky (JURNAL RISET BISNIS DAN MANAJEMEN, 2016)
Based on the result of the F-test, with F count is 47,679 with the significance 0,000. df1 = 4 dan df2 = 75. Is known df1=4 and df2=75 so that the value of F table is 5,68. Because of the value of the significancy is smaler than 0.05 and F count more greather than F table (45,238>5,68), it can be concluded that variable style of leadership, job satisfaction,organization commitment and competition simoustenously has influence and can be use to prediction the performance of civil servant in Maybrat Regency. Leadership style, job satisfaction, organization commitment and competition along the performance of the staff is reliable. It can be seen on positive alpha coeficient with value greater than 0,6. Therefore,the research instrument can be use to examine the similar data in the similar condition, with the probability of the research result that can be trusted. Keywords: Leadership Style, Job Satisfaction, Organization Commitment and competition, and Staff Performance